2015
DOI: 10.1039/c5dt03065j
|View full text |Cite
|
Sign up to set email alerts
|

A new class of deep-blue emitting Cu(i) compounds – effects of counter ions on the emission behavior

Abstract: Three deep blue emitting Cu(I) compounds, [Cu(PPh3)tpym]PF6, [Cu(PPh3)tpym]BF4, and [Cu(PPh3)tpym]BPh4 (tpym = tris(2-pyridyl)methane, PPh3 = triphenylphosphine) featuring the tripodally coordinating tpym and the monodentate PPh3 ligands were studied with regard to their structural and photophysical properties. The compounds only differ in their respective counter ions which have a strong impact on the emission properties of the powder samples. For example, the emission quantum yield can be significantly incre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 100 publications
(266 reference statements)
3
28
0
Order By: Relevance
“…The individual value depends on molecular properties, for example, on the extent of SOC of higher lying singlets to the lowest triplet state, but also on the local environment, such as a fluid or a rigid matrix . In general, a significant prompt fluorescence (S 1 →S 0 ) is not detected, but a very bright long‐lived phosphorescence (T 1 →S 0 ) is frequently observed at low temperature . At higher temperature and in a situation of a fast thermal equilibration, population of the higher lying singlet state is governed by the Boltzmann distribution.…”
Section: Tadf Molecular Parameters and Diversity Of Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…The individual value depends on molecular properties, for example, on the extent of SOC of higher lying singlets to the lowest triplet state, but also on the local environment, such as a fluid or a rigid matrix . In general, a significant prompt fluorescence (S 1 →S 0 ) is not detected, but a very bright long‐lived phosphorescence (T 1 →S 0 ) is frequently observed at low temperature . At higher temperature and in a situation of a fast thermal equilibration, population of the higher lying singlet state is governed by the Boltzmann distribution.…”
Section: Tadf Molecular Parameters and Diversity Of Materialsmentioning
confidence: 99%
“…However, mixing‐in of different, higher lying singlets S n (with n >1) can be significant. If so, the triplet state of Cu I complexes, for example, exhibits a distinct ZFS of several cm −1 (a few 0.1 meV) and the T 1 →S 0 transition rate for the phosphorescence can become as large as 5×10 4 s −1 (20 μs) . Accordingly, a second, effective radiative decay channel is opened in addition to the TADF decay path.…”
Section: Tadf Molecular Parameters and Diversity Of Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our attempts to obtain the unsubstituted ligands E(2-py) 3 (E = As,S b, Bi)u sing the in situ reaction of 2-lithiopyridine with ECl 3 were only successful for E = As, [25] apparently as ar esult of reductive elimination of bipyridine from E(2-py) 3 and the generation of elemental Sb or Bi for the heavier Group 15 elements.T his is in line with ap revious report which showed that the ligand Bi(2-py) 3 could not be obtained even from the reaction of BiCl 3 with the more stable 2-(ZnBr)-pyridine reagent. Our attempts to obtain the unsubstituted ligands E(2-py) 3 (E = As,S b, Bi)u sing the in situ reaction of 2-lithiopyridine with ECl 3 were only successful for E = As, [25] apparently as ar esult of reductive elimination of bipyridine from E(2-py) 3 and the generation of elemental Sb or Bi for the heavier Group 15 elements.T his is in line with ap revious report which showed that the ligand Bi(2-py) 3 could not be obtained even from the reaction of BiCl 3 with the more stable 2-(ZnBr)-pyridine reagent.…”
mentioning
confidence: 97%